The impact of the difference in the significance of the absolute command on obligation in the jurisprudential branches (Analytical, descriptive study) - Al-Warraq, Rahma Abdullah Musleh (Journal of Islamic Sciences, 2023)
This research aims to define the command and its significance، and explain the opinions of scholars in the significance of the absolute command، and clarify the impact of the difference in the significance of the absolute command on obligation in the jurisprudential branches.The researcher adopted the descriptive and analytical approach، and the research was divided into two topics، the first topic is the definition of the absolute command، its formula and its significance، and the second topic is the scholars` opinions on the significance of the absolute command and its impact on the jurisprudential branches. The research has a set of results، most notably:1.It is necessary to know the absolute command of the context and other fundamental issues in order to know the provisions of god that are in the goodness of the nation and to know what is necessary to act in an inevitable way and what is not necessary as well.2. The absolute command that is devoid of the context indicates obligation، and if it has a context، it is carried according to what the context indicates.At the conclusion of the research، the researcher recommend further research on fundamentalist rules due to their importance and the need to know what is obligatory from the provisions of the Shari'a rather than others.
Keywords: impact; difference; command; absolute; branches; jurisprudential